The Role of Income Class and Regional Development in Shaping Pro-Environmental Behaviors in Indonesia - Pattinasarany, Indera Ratna Irawati (Technium Sustainability, 2025)
This study investigates the factors influencing private-sphere pro-environmental behavior (PEB) using a national longitudinal dataset, focusing on income class, provincial macroeconomic conditions, and their interactions. By applying a multilevel mixed-effects logistic model, the research highlights disparities in resource access and the barriers lower-income populations face. The analysis covers three PEB measures: energy conservation, water conservation, and waste management, contributing to a deeper understanding of social stratification's impact on PEB. The findings reveal that higher-income individuals are more likely to conserve water. Lower-middle and upper-middle-income groups conserve energy more frequently yet participate less in waste sorting. Provincial economic conditions significantly shape PEB patterns. A higher Human Development Index (HDI) fosters water and energy conservation and moderates income-based disparities in sustainability practices. These results suggest that financial resources alone do not determine sustainability behaviors, as social norms and habitual practices also play key roles. The study's findings provide policy recommendations to enhance public engagement in PEB, offering a promising path for positive change.